(untitled) (American International Journal of Economics and Finance Research, 2023)
Civil society organizations/Non-governmental organizations complement government efforts and contribute to making life better for the people in their domain. They complement government efforts in making by improving the quality of living standards of the populace. They play an important role in creating awareness for people to know their rights and enhancing issues of accountability, transparency, and good governance by contributing to increased public debates on critical matters concerning the formulation and implementation of governmental policies. As such, they are important partners in deriving economic development in every nation globally. This paper examines the acceptability and applicability of accounting software by civil society organizations within Kano Metropolis. The population consists of 137 CSOs/NGOs operating within Kano Metropolis; the study adopted the population as a sample, primary data was used as the questionnaires were distributed and retrieved with the help of research assistants, and the chi-square (X2) analysis shows that the null hypothesis was rejected. The findings show that finance and accounts staff, including accountants, do not show passion in accepting and applying accounting software to do the financial transactions in their organizations and still prepare to use manual methods of recording financial transactions, which do not conform to the best accounting practice. The study concludes that there is a lack of positive attitude on the part of staff to accept and apply the accounting software to use in their CSOs/NGOs. Hence, this study recommends that proper orientation and training should be given to the CSOs/NGOs staff in the Kano Metropolis to change the narrative. JEL Classification Codes: H83.